Carpal Tunnel Syndrome Diagnostics Revisited: A Comprehensive Review - Stanisław Słyk; Nina Kamińska-Słyk; Izabela Domitrz (International Journal of Clinical Practice)
Carpal tunnel syndrome (CTS) remains the most common peripheral entrapment neuropathy worldwide. There are several challenges associated with CTS diagnostic process. The most widely accepted gold standard is clinical assessment. Its subjective nature and the experience required pose an insurmountable challenge when aiming to achieve satisfactory accuracy and consistency. Nerve conduction and imaging studies are not widely available to general practitioners and have to be performed by specialists, which prolongs the diagnostic process. Meanwhile, the syndrome may progress, leading to the exacerbation of symptoms. Furthermore, the therapeutic decisions have to be well-founded, as invasive surgeries are often considered as the treatment of choice in more severe CTS cases. A resurging alternative method, which shows a lot of promise, is quantitative sensory testing. For the purposes of this review, databases available in Medical University of Warsaw resources were screened and evaluated by two independent reviewers. 29 studies were identified for further assessment. There is a need to reconsider the commonplace trends and establish proper diagnostic guidelines. The available diagnostic methods should be viewed as complementary rather than standalone. Choosing the right combination can provide a more accurate and comprehensive evaluations of CTS, helping to confirm the diagnosis, assess severity, and guide treatment options.